The Effect of Biofertilizer on The Diversity of N2O Reducing Bacteria in Paddy Fields of Sukabumi, Indonesia - Alfan Cahyadi; Iman Rusmana; Nisa Rachmania Mubarik (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
Some of the methanotrophic bacteria and N2O reducing bacteria have been proven to be able to support the plant growth and increase the productivity of paddy. However effect of the methanotrophic and N2O reducing bacteria application as a biofertilizer to indigenous N2O reducing bacteria is still not well known yet. The aim of this study was to analyze the diversity of N2O reducing bacteria in lowland paddy soil based on a nosZ gene. Soil samples were taken from lowland paddy soils in Pelabuhan Ratu Sukabumi, West Java, Indonesia. There were two treatments for the paddy field soil, ie. biofertilizer-treated field 20% fertilizer (50 kg/ha) with the addition of biofertilizer and 100% fertilizer. PCR amplification of nosZ gene was successfully conducted using nosZF and nosZR primer pair. Denaturing Gradient Gel Electrophoresis (DGGE) process was conducted at 150 V for 5.5h. There were three differences nosZ bands were sequenced. The phylogenetic analysis showed that they were close to uncultured bacteria. Microbial diversity in the biofertilizer-treated field was higher than that of in the 100% fertilizer-treated field. The biofertilizer treatment has higher in microbial diversity than that of applied non-biofertilizer paddy fields. This research might have impact in the application of biofertilizers due to the emission of N2O as a green house gas from paddy fields farming activity. The biofertilizer has great potential application in sustainable environmental friendly agriculture systems.